FEASIBILITY OF THE UTILIZATION CONDENSATE AS RAW MATERIAL FOR PETROCHEMICAL - Holisoh Holisoh (Scientific Contributions Oil and Gas, 2016)
The utilization of condensate is currently not optimal yet, where most of its production are mixed with crude oil which results in significant shrinkage in oil volume. As a hydrocarbon product, condensate can be utilized as a raw material for petrochemical industry, fuel and solvent. Currently raw materials of petrochemical industry in Indonesia are imported from other countries. To optimize the utilization of condensate it is necessary to conduct a characteristic test of several types of condensate and then conducted a utilization analysis based on their number and its nature. Paraffin, Olefin, Naphthenic and Aromatic (PONA) test results showed that the six samples of condensate in the test had a fairly high paraffin content of above 60%. The highest paraffin content was 82.84% for condensate B and the lowest was 61.4% for condensate E. The six condensate samples contain higher paraffin, which are suitable for use as raw material for petrochemical olefin.The results of the economic calculation of the construction unit Olefin Process Center with a capacity of 100,000 BPSD, which is an IRR as 22.8 %, the NPV as of US $ 1,801,491,951.12 , POT for 4.1 years, and PI as 1.87. Developing of Olefin Process Unit Center being constructed in Indonesia is economical worthy.